LITERASI KEUANGAN SYARIAH SEJAK DINI SEBAGAI UPAYA PENINGKATAN MARKET SHARE PERBANKAN SYARIAH: PADA SANTRI PONDOK PESANTREN FADLILATUL MUNNA, MAGELANG - Agep Rumanto; Mahilda Vitriani (LPPI UMN AL WASHLIYAH, 2026)
The community service initiative at Pondok Pesantren Fadlilatul Munna, Magelang, focused on boosting Islamic banking market share through early financial literacy. The program aimed to transform students into agents of change for Indonesia's Sharia economy. Execution & Content: Using a structured approach (pre-test, presentation, Q&A, and post-test), experts Arif Mulyawan and Rahmatul Arifin educated participants on: Core Principles: Prohibitions on riba (usury), gharar (uncertainty), and maisir (gambling). Practical Application: The use of Sharia contracts (akads) in economic activities. Results: While initial knowledge was low, post-test results showed significant improvement. Students engaged deeply, asking critical questions about banking costs and the Sharia status of cryptocurrencies. Conclusion: Early education is a strategic necessity for the Islamic finance sector. The program recommends expanding these efforts to more youth to ensure the long-term growth of the Sharia financial ecosystem.